Community Engagement and Planning versus Resources for Services for Implementing Depression Quality Improvement: Exploratory Analysis for Black and Latino Adults - Barceló, Nicolás E. (Ethn Dis, 2019)
OBJECTIVE: Racial/ethnic minorities experience disparities in depression1 and there is a paucity of evidence-based interventions to improve depression care access and outcomes. Community Partners in Care (CPIC) is a community-partnered study of depression care quality improvement (QI) in under-resourced, urban communities: Community Engagement and Planning (CEP) for multi-sector coalitions, and Resources for Services (RS) for program technical assistance.2 CEP demonstrated benefits for the overall CPIC study population; effects for Black and Latino sub-populations are unknown. METHODS: This sub-analysis examines outcomes for 409 Latino and 488 Black (non-Latino) adults recruited from 90 programs who completed baseline or 6-month follow-up. Regression analyses were used to estimate CEP vs RS intervention effects on primary (Mental Health Related Quality of Life [MHRQL], Patient Health Questionnaire-9 [PHQ-9]) and community-prioritized (mental wellness, physical activity, risk for homelessness) outcomes at 6-months RESULTS: Baseline characteristics did not differ significantly by intervention in either group. In the adjusted analysis for Black adults, CEP resulted in decreased odds of poor MHRQL (OR: .62, 95% CI=.41-.94, P=.028) with a trend for reducing homelessness risk (OR: .60, .35-1.05, P=.69). For Latino adults, CEP resulted in greater probability of mental wellness (OR: 1.81, 1.05-3.13, P=.034) and a trend for increased physical activity (OR: 1.52, .93-2.49, P=.091). CONCLUSIONS: Exploratory analyses of CEP for depression quality improvement suggests significant 6-month benefits in mental health outcomes for Black and Latino participants and trends for improvement in community-prioritized outcomes for both groups. Findings may inform research in multi-sector coalitions to promote equity in depression care.